Analyzing the impact of foreign capital inflows and political economy on economic growth: An application of regime switching model - Nabila Khurshid; Hamza Sharif; Mosab I. Tabash; Basem Hamouri; Asma Fiaz; Fozia Munir (Economies, 2023)
The goal of this study is to use the Markov Regime Model (MSM) to evaluate the impact of three important FCIs and the political economy on Pakistan's economic growth. The current research used quarterly data from 2000 to 2020. The empirical results demonstrate that dictatorship contributes favorably to the high and low growth regime of the economy, while election time contributes positively to the expansion period and adversely in recession times of the economy. Results confirmed that external debt has a strong negative influence on economic growth in both the high and low-growth regimes. Remittances, FDI, and growth, on the other hand, have a positive and substantial link with economic growth. This research suggested that effective fiscal and monetary policies, as well as a suitable political environment, should be provided so that foreign investors would be enticed to invest in Pakistan
Keywords: 330; foreign capital inflows; political economy; election time; Markov Switching Model; Pakistan